Phytoestrogen Genistein and Black Cohosh and Marker of BMD in Menopausal Women - Rizani Amran; Adenan Abadi; Theodorus Theodorus; Elvi Widiastuti (MEDIA MEDIKA INDONESIANA, 2012)
Background: In Indonesia, phytoestrogens can be found in the market as supplement to resolve climacteric complaint and osteoporosis. This phytoestrogens has not been proven scientifically to have benefit in overcoming the climacteric complaints and osteoporosis in menopausal women. Therefore, it is important to have clinical test searching data for knowing the increase of bone mineral density (BMD).Methods: The design was comparison clinical test in the form of “add on” with double blind in Hospital of Mohammad Hoesin Palembang started in August 2010 until February 2011 putting subjects into fitoestrogen and placebo groups randomly. T-score of spine and femur were measured using done densitometry before and after 6 months supplementation.Results: In the beginning of study, it was found that the average of spine T-score in the group of phytoestrogens was -1.455±0.264 after 6 months it increased to -1.295±0.223 with change 0.160±0.153 (p=0.001).Whereas in placebo group the average of spine T-score at the beginning of the study was -1.295±0.223 becoming -1.560±0.414 with decrease of -0.100±0.273 (p=0.118). Femur T-score level, of phytoestrogens group at the beginning of the study was -1.415±0.215, after 6 months it became -1.270±0.141 with change of 0.145±0.170 (p=0.001). In placebo group, the average of femur T-score was -1.475±0.202 becoming -1.595±0.421 with of decrease -0.120±0.33 (p=0.124). The status of spine and femur T-score BMD both in, phytoestrogens and placebo group was osteopenia at the beginning of the study. After 6 months, spine T-score in phytoestrogens group did not change, and in placebo group, 2 subject showed osteoporosis with spine T-score and femur T-score -2.7 and -2.75(±0.212).Conclusions: The administration of phytoestrogens is able to maintain bone mineral density and prevent the occurrence of osteoporosis.Keywords: Phytoestrogens, BMD, T-score, menopauseABSTRAK Fitoestrogen genistein dan black cohosh dan penanda BMD pada perempuan menopauseLatar belakang: Di Indonesia, fitoestrogen beredar di pasaran sebagai suplemen untuk mengatasi keluhan klimakterik dan osteoporosis. Fitoestrogen ini belum terbukti secara ilmiah bermanfaat untuk mengatasi keluhan klimakterik maupun osteoporosis pada perempuan menopause. Oleh karena itu uji klinik ini dilakukan untuk mencari data guna mengetahui meningkatnya gambaran BMD.Metode: Desain adalah uji klinik berpembanding dalam bentuk add on, secara tersamar ganda di RS Dr. Mohammad Hoesin Palembang bulan Agustus 2010 sampai dengan Februari 2011 pada subyek yang dibagi dalam kelompok fitoestrogen dan placebo secara acak. Variabel yang diukur adalah skor T tulang vertebra dan femur menggunakan bone densitometer sebelum dan setelah 6 bulan mendapat suplemen.Hasil: Pada awal penelitian rerata T-skor tulang belakang kelompok fitoestrogen -1,455±0,264 setelah 6 bulan menjadi -1,295±0,223 dengan perubahan 0,160 ± 0,153 (p=0,001). Sedangkan kelompok plasebo rerata T-skor tulang belakang pada awal penelitian -1,295±0,223 menjadi -1,560±0,414 dengan penurunan -0,100±0,273 (p=0,118). Pada kadar T-skor femur, di awal penelitian kelompok fitoestrogen -1,415±0,215 setelah 6 bulan menjadi -1,270±0,141 dengan besaran perubahan 0,145±0,170 (p=0,001). Pada kelompok plasebo rerata T-skor femur pada awal penelitian -1,475±0,202 menjadi -1,595±0,421 dengan perubahan -0,120±0,33 (p=0,124). Status BMD T-skor tulang belakang dan femur di awal penelitian, kelompok fitoestrogen dan kelompok plasebo adalah osteopeni. Setelah 6 bulan kemudian, pada kelompok fitoestrogen tidak terdapat perubahan status BMD sedangkan pada kelompok plasebo terdapat 2 orang yang densitas mineral tulangnya mengalami perubahan menjadi osteoporosis dengan rerata T-skor tulang belakang -2,70 dan T-skor femur -2,750 ± 0,212.Simpulan: Pemberian fitoestrogen dapat mempertahankan densitas mineral tulang dan mencegah terjadinya osteoporosis.